The significance of physical activity in behavioral management of type 2 diabetes. Interventions and Improving Outcomes in Type 2 Diabetes Management: The significance of physical activity - Czapska, Mirella; Wojcik, Alicja; Pakaszewski, Wojciech; Krawczyk, Lidia; Kwiecień, Bartłomiej; Babkiewicz-Jahn, Kamila; Matuszewska, Justyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose Diabetes is a set of metabolic disorders whose common, characteristic feature is the occurrence of hyperglycemia. Elevated glycemia levels result from impaired insulin secretion and/or defects in its action. In type 2 diabetes, we have modified risk factors such as improper diet, reduced physical activity, and obesity. In the context of these reversible factors, intervention in patients’ lifestyle, with particular emphasis on physical activity, seems advisable. To investigate the implementation of recommendations for the treatment of type 2 diabetes, relating to physical activity as a component of behavioral treatment of diabetes. Materials and methods. Author’s survey covering patients’ knowledge about their disease, needs and expectations regarding education. The questionnaire examines the physical activity of patients newly diagnosed and already treated for type 2 diabetes. Results. The most frequently undertaken exercise was of medium intensity in the form of walking or "Nordic walking". This was also more likely to be intensified. Patients choosing this type of activity practiced it much more often and more regularly than other types of activity. Running and cycling were other activities undertaken by the patients, although in the younger group of patients. Patients who enjoyed physical exercise were more likely and willing to do it and it was more regular. Conclusions. Patients were reluctant to undertake physical exercise and usually did not treat it as an integral part of treatment. Usually, it was not a very intense effort. They also rarely intensified it when the diagnosis was made. Most of the respondents did not understand the role of exercise in the treatment process and its impact on sugar levels.